Backward-facing step heat transfer of the turbulent regime for functionalized graphene nanoplatelets based water–ethylene glycol nanofluids. (June 2016) - Amiri, Ahmad; Arzani, Hamed Khajeh; Kazi, S.N.; Chew, B.T.; Badarudin, A.
Highlights: Introducing a promising method for functionalization of GNP. Preparing of GNP-based water–ethylene glycol nanofluids. Investigation of the thermophysical properties of the synthesized samples. Prediction of the convective heat transfer and performance index. Numerical investigation of heat transfer in an backward-facing step. Abstract: Herein, an experimental study on thermo-physical properties of ethylene glycol-functionalized graphene nanoplatelets/water–ethylene glycol nanofluids (EGGNP-WEG) and a numerical study on the convective heat transfer over a backward-facing step are performed. Accordingly, EGGNP was first synthesized covalently to achieve a stable colloidal solution in water–ethylene glycol mixture. Some characterizations were applied to analyze the surface functionality and morphology of EGGNP-flakes. To study the convective heat transfer coefficient in turbulent regime, a numerical study is performed at different weight fractions of EGGNP. According to the results, a higher weight concentration of EGGNP in basefluid indicates a greater extent of convective heat transfer coefficient and thermal conductivity, implying higher heat transfer rate over a backward-facing step.